IMPLEMENTATION OF GENDER MAINSTREAMING IN WOMEN'S PROTECTION POLICY IN SIAK DISTRICT - Firdaus, Emilda; Andrikasmi, Sukamarriko; Haryono, Dodi; Indra, Mexsasai; Artina, Dessy; HB, Gusliana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Women are a group or group that is vulnerable to violence that occurs in society. To overcome various issues of violence that occur against women, special attention is needed from all groups, both community groups and government circles, consisting of the central government and regional governments. This certainly has an impact on the existence of women's groups in the social order amidst demands for achieving Sustainable Development Goals (SDG's). If we refer to the concept of